Decarbonization Strategies and Operational Excellence in Maritime Shipping: A Systematic Analysis of Green Shipping Implementation and Performance Management - Meilinasari Nurhasanah Hutagaol; Jarot Delta Susanto; Sursina Sursina; Muhammad Nurdin; Ardiansyah Ardiansyah (Fundamental and Applied Management Journal, 2026)
The global maritime shipping industry faces unprecedented pressure to reconcile operational efficiency with environmental sustainability, particularly in response to the International Maritime Organization's ambitious decarbonization targets for 2050. This study systematically analyzes the implementation of green shipping strategies and performance management frameworks within the maritime sector, focusing on the intersection of strategic operations management and corporate social responsibility. Employing a qualitative research design grounded in thematic analysis, cross-group comparison, and narrative synthesis, the study draws upon document analysis and structured expert consultations involving maritime industry professionals, academic researchers, and institutional stakeholders. The findings reveal that effective decarbonization in maritime shipping requires an integrated approach combining technological innovation, regulatory compliance, organizational culture transformation, and multi-stakeholder governance. Three principal themes emerged: the centrality of knowledge management in sustainability transitions, the mediating role of performance evaluation systems in bridging strategic intent and operational outcomes, and the critical importance of adaptive decision-support frameworks for managing trade-offs among environmental, economic, and social objectives. The study contributes to the literature by proposing a conceptual model that links green shipping implementation to operational excellence through sustainability-oriented performance management, offering actionable insights for policymakers, shipping companies, and maritime education institutions.